2013
DOI: 10.1063/1.4826476
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of heat transfer augmentation due to mechanical distortions in hypervelocity boundary layers

Abstract: We examine the response of hypervelocity boundary layers to global mechanical distortions due to concave surface curvature. Surface heat transfer and visual boundary layer thickness data are obtained for a suite of models with different concave surface geometries. Results are compared to predictions using existing approximate methods. Near the leading edge, good agreement is observed, but at larger pressure gradients, predictions diverge significantly from the experimental data. Up to a factor of five underpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…It can be seen that the density on the concave surface increases in the main stream and in the boundary layer downstream of the turning point, and also that compression waves become evident as curvature radius decreases. As measured in previous studies (Fernando & Smits (2006), Donovan et al (1994), Spina et al (1994), Flaherty & Austin (2013a), Wang et al (2016b)), the boundary layer thickness decreases on a concave wall and on a flat plate with adverse pressure gradient in a supersonic flow. In contrast to this, recent by nano-particle planar laser scattering visualizations of the instantaneous two-dimensional flow Wang & Wang (2016) observed that the concave boundary layer becomes thicker.…”
Section: Thermal Effectssupporting
confidence: 77%
See 3 more Smart Citations
“…It can be seen that the density on the concave surface increases in the main stream and in the boundary layer downstream of the turning point, and also that compression waves become evident as curvature radius decreases. As measured in previous studies (Fernando & Smits (2006), Donovan et al (1994), Spina et al (1994), Flaherty & Austin (2013a), Wang et al (2016b)), the boundary layer thickness decreases on a concave wall and on a flat plate with adverse pressure gradient in a supersonic flow. In contrast to this, recent by nano-particle planar laser scattering visualizations of the instantaneous two-dimensional flow Wang & Wang (2016) observed that the concave boundary layer becomes thicker.…”
Section: Thermal Effectssupporting
confidence: 77%
“…Figure 25(b) shows the inner region flow interaction with adverse pressure gradient, which also represents the boundary layer interaction with the adverse pressure gradient without centrifugal effects. As given in the previous studies (Fernando & Smits 1990;Donovan et al 1994;Flaherty & Austin 2013b;Wang et al 2016a), the boundary layer thickness on the flat plate decreases when subject to adverse pressure gradient. Comparing figure 25(a)-(b), the prominent difference is that the Görtler vortices induce stretching, twisting and distortion of the density gradient surfaces .…”
Section: Iso-surfaces and Slices Of Instantaneous Velocity In Three-dsupporting
confidence: 53%
See 2 more Smart Citations
“…Wang et al (2016a) found that the principal strain rate had different streamwise varying trends at different wall-normal locations. Flaherty & Austin (2013) examined the surface heat transfer of a hypersonic concave boundary layer with Mach number up to 7.45. They found significant augmentation in the surface heat transfer over the baseline flat plate.…”
Section: Introductionmentioning
confidence: 99%